The CBA analysis of IFRS implementation in the Czech Republic - Honková, Irena (Masarykova univerzita, 2019)
As part of the ongoing harmonization of accounting system there is an increasing tendency to keep the accounts under IAS/IFRS. Consequently, a research in companies following the IAS/IFRS has been conducted. The aim of the research was to identify information, financial and time demands and also the benefits of the IAS/IFRS implementation. It was found that more companies use the services of an external consultant than an internal employee. Businesses normally do not share their knowledge. The costs of the implementation process are most often up to 100 thousand Euros, but most businesses acknowledged additional unquantified costs. The duration of the implementation process was to one year. There are different views of the respondents on the level of individual standards. Most respondents admitted making mistakes in the first years of the implementation, but these were rather minor flaws. Regarding the perceived benefits, the majority of respondents agreed that the IAS/IFRS enable good comparability. However, when it comes to their brand and financial statements, they stated that for the company’s reputation the brand was more important than financial statements. It was found, however, that the majority of businesses have not experienced a reduction in the cost of capital.
Cost-benefit analýza implementace IFRS v České republice
Keywords: International Financial Reporting Standards (IFRS); International Accounting Standards (IAS).; Mezinárodní standardy finančního výkaznictví (IFRS); mezinárodní účetní standardy (IAS).